2008
DOI: 10.1177/0961203308091287
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones supplementation alleviates disease severity in autoimmune-prone MRL-lpr/lpr mice

Abstract: Soy isoflavones supplements, which are phyto-oestrogens widely used as alternatives to alleviate menopausal syndromes or prevent chronic diseases, may exert oestrogenic and anti-oestrogenic activities. This study aimed to investigate the effects of soy isoflavones supplement on oestrogen-related autoimmune disease, such as systemic lupus erythematosus, using autoimmune-prone female MRL-lpr/lpr mice. Eighty mice of 8 weeks were divided into five groups: 0 (Control), 2 (Isf 2), 10 (Isf 10) and 20 (Isf 20) mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
4
13
0
1
Order By: Relevance
“…Because soybean-based foods have high levels of isofl avones, whose structure is similar to that of 17β-estradiol (E2), they have estrogenic effects and reduce proteinuria and the renal lesions associated with progressive renal failure. 17,32 However, potent adverse effects of isofl avones on the immune response of mice have also been reported. 33 Zhao et al 33 have reported that a soybean-rich diet can exacerbate renal damages, increasing serum creatinine and reducing the creatinine clearance, which increase the severity of the glomerular disease in MPL/lpr mice.…”
Section: Isofl Avonesmentioning
confidence: 99%
See 3 more Smart Citations
“…Because soybean-based foods have high levels of isofl avones, whose structure is similar to that of 17β-estradiol (E2), they have estrogenic effects and reduce proteinuria and the renal lesions associated with progressive renal failure. 17,32 However, potent adverse effects of isofl avones on the immune response of mice have also been reported. 33 Zhao et al 33 have reported that a soybean-rich diet can exacerbate renal damages, increasing serum creatinine and reducing the creatinine clearance, which increase the severity of the glomerular disease in MPL/lpr mice.…”
Section: Isofl Avonesmentioning
confidence: 99%
“…The results have shown that soybean can accelerate glomerulonephritis, but improves the proliferative function of T cells. 33 On the other hand, Hong et al 32 have shown that the supplementation with isofl avones increased the survival of SLE murine models, inhibiting the production of autoantibodies (anti-dsDNA and anticardiolipin), and reducing the secretion of IFN-γ. Those authors have also reported that isofl avones have anti-infl ammatory properties and antioxidant effects.…”
Section: Isofl Avonesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, soy isoflavones supplements, which are phyto-oestrogens widely used as alternatives to alleviate menopausal syndromes or prevent chronic diseases, may exert oestrogenic and anti-oestrogenic activities. Hong et al (2008) reported a significant increase in the oestrogenic activity of the methanol extracts of soy isoflavones for oestrogen receptor (ER) , but not (ER) , suggesting that soy isoflavones have a selective modulation of ER activation. The soy isoflavone supplementation did not aggravate murine lupus, but apparently ameliorated the disease.…”
Section: Soybean In Monogastric Animal Nutrition and Healthmentioning
confidence: 99%